Celebrating the American home : 50 great houses from 50 American architects - Bouknight, Joanne Kellar (Taunton Press, 2005)
Celebrating the American Home brings together the best 50 houses featured in books from the Taunton Press in the past five years. These houses, which range from the irresistibly cozy to the magisterial to the daringly innovative, were selected by a panel of distinguished residential architects who are members of the American Institute of Architects including Jeremiah Eck, Duo Dickinson, and John Connell, who chose the houses based on how well they reflected the core qualities of great home design. Each house is showcased in four to six pages and shown from a variety of views, with a brief introductory text explaining what makes the house unique and color photographs illustrating the key design features. Sidebars elaborate on why the architects selected each house, while an introductory chapter provides a detailed explanation of those core qualities that distinguished a great home: human-size scale, livability, quality of craft, connection to site, and distinctive design.